2002
DOI: 10.1295/polymj.34.539
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure of Isotactic Polypropylene Formed from Homogeneous Solution. Gelation and Crystallization

Abstract: ABSTRACT:The molecular structure and morphology grown from isotactic polypropylene (iPP)/o-dichlorobenzene solution were investigated by thermal analysis and high-resolution solid-state 13 C NMR. The morphology varied depending on incubated temperature. A gelation occurred below 70• C, while the crystallization took place over 80• C. The crystal obtained was identified with the α-form, which is the most stable crystalline modification of iPP. In CP/MAS 13 C NMR spectrum, the chemical shift of methylene, methin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Here, we instead observe by WAXD a conversion of PP mesophase to α crystal phase, in a manner consistent with the change in mechanical properties. SSNMR spectra acquired on the same samples are compatible with the mesophase reported for iPP films crystallized with very large overcooling (100 °C) or where disorder is inserted by the presence of solvents but do not show significant amount of crystallographically pure α phase.…”
Section: Discussionsupporting
confidence: 68%
“…Here, we instead observe by WAXD a conversion of PP mesophase to α crystal phase, in a manner consistent with the change in mechanical properties. SSNMR spectra acquired on the same samples are compatible with the mesophase reported for iPP films crystallized with very large overcooling (100 °C) or where disorder is inserted by the presence of solvents but do not show significant amount of crystallographically pure α phase.…”
Section: Discussionsupporting
confidence: 68%
“…[7][8][9] SBS oil gel is applied as constructing materials and shock absorber for its rubbery elasticity. The gel networks of SBS in oil is formed by the aggregative interaction of the styrene units in a selective solvents which is a good solvent for butadiene units, but a poor solvent for styrene unit, and seggregative interaction between the styrene and butadiene units.…”
Section: Introductionmentioning
confidence: 99%
“…The gel-forming crystal possibly takes a disordered form. 4 Most investigations on gel have focused on details of the sol-gel transition, but some are concerned with the coagulation and melting behavior of the solvent in the gel. Higuchi et al investigated the melting behavior of water in a polyvinyl alcohol (PVA) swollen gel, and showed the existence of free water and freezable bound water.…”
Section: Introductionmentioning
confidence: 99%
“…Gelation of a crystalline polymer such as isotactic polypropylene (iPP) is closely associated with the formation of crystal as a cross-linking point. [1][2][3][4][5] Okabe et al reported a solgel transition and the morphology of iPP gel by thermal analysis and polarizing microscopy, 6,7 and found that the gel melting temperature is fitted as a function of polymer concentration by a Eldridge-Ferry plot and many spherulites exist in the gel. There exist three types of crystalline modification.…”
mentioning
confidence: 99%
See 1 more Smart Citation